Women's resource directory. - Philippines. National Commission on the Role of Filipino Women (Manila National Commission on the Role of Filipino Women, 1989)
It contains profiles of different women non-governmental organizations (NGOs) and other development agencies with women-related concerns.
Fi-1252g donated by Prof. Mamoru Tsuda, M.A., U.P., 1977.
Keywords: Women -- Societies and clubs -- Philippines -- Directories; Women -- Services for -- Philippines -- Directories